EFEKTIVITAS MEDIA SOSIAL DAN KOMUNIKASI WHATSAPP DALAM PERLINDUNGAN PEKERJA MIGRAN INDONESIA DI TAIWAN - Rumintjap, Merdy Ervina (Istek Widuri Jakarta, 2019)
Indonesian Migrant Workers (PMI) are groups of workers who work abroad. Indonesia as a country that has a large workforce with a majority of low education, has difficulty in providing decent employment in the country, so working abroad is a choice for millions of PMI in an effort to improve and answer life's needs.As a country sending large migrant workers, PMI needs protection relating to their rights and obligations as PMI, both before placement, placement period and post placement. Even though there is a regulation that states that every PMI who wants to work abroad must get knowledge of the country where they work, this facility is considered inadequate to provide PMI abroad.Facilities that are considered very comfortable and easy to protect PMI can be done through social media facilities. Along with the fact that all PMIs have cellular phones, the use of social media is considered to be more effective in reaching more people, cheaper, more convenient, able to access the latest news and easy to share (viral). Just as it is currently done by PMI in Taiwan every time a PMI wants to find and provide information to others PMI.